Mårten Magnus Wilhelm Brenner, Finnish plant enthusiast - Väre, Henry (Societas pro Fauna et Flora Fennica, 2021)
Mårten Magnus Wilhelm Brenner (1843–1930) was a controversial figure in Finnish botany. He was a passionate non-professional botanist, amongst the most diligent Finnish writers of his time having published 220 articles or notes. He described 833 taxa, including 411 species, six subspecies, 196 varieties, four subvarieties, 199 forms and 17 subforms. Typifications of 151 names are provided in a separate article. Brenner was particularly interested in the Hieracium taxonomy, but he studied several other plant genera and species during almost 60 years of botanical activity: Alnus, Erophila [Draba] verna, Euphrasia, Juncus, Linnaea borealis, Picea abies, Pimpinella saxifraga, Primula officinalis [veris], Rosa, Sorbus aucuparia, Taraxacum and Viola tricolor, for example. His descriptions resulted largely from his own collection activity without any synoptic work. Typically, each taxon was based on small, minor details, sometimes on a single or a few specimens, and often characterised by local distribution. Producing detailed infraspecific classifications was common practice in those times, apparently inspired by the German school of taxonomy, which was later called the Aschersonian approach. For many obvious reasons, botanists of that and later eras did not appreciate Brenner’s taxonomic results. Only some Euphrasia (one taxa), Hieracium (11) and Taraxacum (20) names are currently accepted in the Checklist of Finnish vascular plants, and E. wettstenii var. botniensium has recently been recognised. Brenner’s interest was not restricted to vascular plants. He collected an amount of lichens in late 1869 and 1870 on the island of Suursaari in the Gulf of Finland, for example, and he published extensive floristic accounts of Suursaari and northern Finland. He focused also on ecology and was concerned about changes in nature resulting from human activity. In northern Finland he collected bryophytes, many of which were new to Northern Ostrobothnia. He wrote a review of the history of lichenology in Finland, which the ...